Influence of Chronic Alcohol Use on Osteoblastic Differentiation of Bone Marrow Cells, Bone Properties, and Hepatic and Renal Morphology of Rats - Michelle Cardoso de Sousa; Mariana Raquel da Cruz Vegian; Matheus Alves Biserra; Bruno César Almeida Costa; Samira Esteves Afonso Camargo; Sigmar de Mello Rode; Carolina Judica Ramos; Luciane Dias de Oliveira; Luana Marotta Reis de Vasconcellos (The Scientific World Journal)
Chronic alcohol exposure can affect the osteoblastic activity and the proliferation and differentiation of cells due to its toxic effect, which can affect negatively bone repair and bone microarchitecture. The aim of this study was to evaluate the effects of chronic use of 20% alcohol on rats regarding osteoblastic differentiation, extrinsic and intrinsic properties of the tibia, and hepatic and renal morphology. Wistar rats were divided into three groups (n=9) in accordance with a 24-week diet. After euthanasia, kidneys, liver, and tibias were removed for analysis and femurs mesenchymal cells were collected. The results showed that chronic use of 20% alcohol influenced neither the alkaline phosphatase production nor total protein (p>0.05) in rats, with similar formation of nodules in all groups (p>0.05). However, significant changes in the liver and kidneys and adverse effects on the mechanical properties of the tibia were observed. According to the results, it can be concluded that the chronic use of alcohol for 24 weeks had no negative influence on the activity and differentiation of osteoblasts, but the mechanical properties of the tibia were impaired and the organs responsible for metabolism and excretion were also affected due to the consumption of alcohol.